Reestruturação do layout de um setor baseado no conceito de fluxo contínuo do Lean Manufacturing - Galera, Natieli Maria (2018)
The companies have been in constant search for cost reduction and productivity improvement. The layout is one of the most fundamental aspects of the productive environment of an organization. A suitable layout provides benefits such as better productivity and reduction of transport-related waste and unnecessary movement. The purpose of this article is to perform a restructure the layout of a productive sector of a food company. The restructuring of the layout was based on the concept of the continuous flow of lean manufacturing. The study was conducted in the operating sector: special cakes cell, which has six employees. First, information was obtained from three main products manufactured in the cell of special cakes, considering the initial layout and production time. Then, was proposed a balancing of production, an organization of employees and a restructuring of the layout . With the change of the cell layout , special cakes presented a 52% increase in productivity in the three studied products.